Preconcentration of rutin at a poly glutamic acid modified electrode and its determination by square wave voltammetry - Santos, Daniela P. [UNESP]; Bergamini, Marcio F. [UNESP]; Santos, Vania A. F. F. M. [UNESP]; Furlan, Maysa [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Taylor & Francis Inc, 2007)
The voltammetric determination of rutin in 0.04 mol l(-1) B-R buffer (pH 4.0) by square wave voltammograms (+0.41 V vs. Ag/AgCl(sat.)) at a poly glutamic acid modified glassy carbon electrode was found to be several orders of magnitude lower than that on a bare glassy carbon electrode. Rutin can be preconcentrated on the films of poly glutamic acid and presented linear relationship from concentration of 7 x 10(-7) to 1 x 10(-5) mol l(-1) in 0.04 mol l(-1) B-R buffer pH 4.0. The method was successfully applied to the determination of rutin in pharmaceutical formulation without any pretreatment.
Keywords: antioxidant determination; modified electrode; poly glutamic acid; rutin